Verbal representation of the concept harvest in Ukrainian and French (on the material of lexicographical sources XIX century) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article deals with the verbal representation of the concept harvest as one of basic units in Ukrainian and French linguocultures. The research is based on the material of lexicographical sources XIX century, in Ukrainian and French. The main and additional features are studied in both languages and the group of ceremonial and ritual nominations is selected.
Keywords: concept; anthropocentrism; ethnic consiousness; internal form